2012
DOI: 10.1371/journal.ppat.1002611
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Superinfection in Women Broadens and Strengthens the Neutralizing Antibody Response

Abstract: Identifying naturally-occurring neutralizing antibodies (NAb) that are cross-reactive against all global subtypes of HIV-1 is an important step toward the development of a vaccine. Establishing the host and viral determinants for eliciting such broadly NAbs is also critical for immunogen design. NAb breadth has previously been shown to be positively associated with viral diversity. Therefore, we hypothesized that superinfected individuals develop a broad NAb response as a result of increased antigenic stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 51 publications
3
76
0
Order By: Relevance
“…Two recent studies have shown that superinfection resulted in greater neutralizing breadth and potency (46,47). In one of these studies, broad and potent NAb responses developed in 2 elite neutralizers very soon after infection with a second virus, suggesting that the development of breadth was accelerated through superinfection (46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent studies have shown that superinfection resulted in greater neutralizing breadth and potency (46,47). In one of these studies, broad and potent NAb responses developed in 2 elite neutralizers very soon after infection with a second virus, suggesting that the development of breadth was accelerated through superinfection (46).…”
Section: Discussionmentioning
confidence: 99%
“…In one of these studies, broad and potent NAb responses developed in 2 elite neutralizers very soon after infection with a second virus, suggesting that the development of breadth was accelerated through superinfection (46). Whether a similar situation provoked the exceptional breadth in CAP256 is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, peak NAb breadth has also been positively correlated with contemporaneous gp160 clonal diversity (Euler et al, 2012). A positive correlation has also been reported between HIV-1 dual infection (which greatly increases env population diversity) and the development of NAb breadth (Cortez et al, 2012). In the present study, we leveraged the greater resolution of next generation sequencing (NGS) to examine the associations between viral genetic diversity and NAb breadth and potency in a well-characterized, antiretroviral therapy (ART)-naive cohort of individuals followed after primary infection.…”
Section: Introductionmentioning
confidence: 91%
“…Previous analysis of high-risk women in Kenya found a significantly lower rate of SI compared to primary incidence (6). HIV SI can significantly impact HIV disease markers by increasing the HIV viral load temporarily or lastingly, by possibly accelerating disease progression, and by putatively increasing HIV-specific antibody responses (3,4,7,8).…”
mentioning
confidence: 99%